Differences of physical literacy perception of kindergarten teachers: Seen from demographic information - Gita Febria Friskawati; Jeane Siti Dwijantie (UIR Press, 2022)
Physical literacy must be instilled in early childhood education, and teachers have a crucial role in this. The aim of this study is to reveal early childhood education teachers' physical literacy perceptions in terms of demographic information. The survey research was conducted with a population of 74 teachers in West Java with convenience sampling. The Perceived Physical literacy Instrument (PPLI) was used as an instrument to measure it. This instrument was distributed through a Google form and filled out voluntarily by the participants. The analysis of the data used is descriptive analysis. The results of this study reveal that teachers with a younger age, teaching experience of 11–20 years, coming from bachelor's degree graduates, and teaching in urban areas have a high perception of physical literacy compared to the demographic status of other teachers. There is a need for special education and training programs for early childhood education teachers in designing learning scenes that are adapted to the concept of physical literacy and are able to harmonize it according to the level of growth and development of children, so that teachers can be formed from an early age. The unrepresentative sample in this study is a limitation that can be used as a recommendation for further research to reveal the perceptions of early childhood education teachers on physical literacy in Indonesia.